(untitled) (Editora Impacto Científico, 2025)
Wheat is a grass-type plant that is grown almost everywhere in the world. It is widely used in the production of many food products, with growing interests by the the brewing industry. In this context, the way by how grains’ physical properties change over the hydration has become essential to design processes and equipments involved in the malting steps. Thus, the objective of this work was to evaluate the influence of moisture content (14.40–90.90% dry basis) on the physical properties (dimensions, porosity, surface area and density) of wheat grains. Moreover, different mathematical models were tested to fit the experimental values. It was found that most of the physical properties varied significantly (p <0.05) with increasing moisture content and were well correlated by means of a second order polynomial model. In this way, because wheat is one of the main grains produced in the world, these results are important for to design safer and more efficient equipment and to improve processes that involve this type of grain. DOI: https://doi.org/10.56238/edimpacto2025.085-003